Clarifying Criminological and Social Psychological Theory: A Second Look at the Relationship between Injustice and General Strain Theory. Issue 2 (February 2014) - Scheuerman, Heather L.
Abstract Research in social psychology and criminology reveals a great deal of overlap when explaining the relationship between injustice and criminal or deviant behavior. The organizational justice literature examines how the major forms of justice (distributive, procedural, and interactional) combine and interact to influence criminal or deviant behaviors in the workplace. While general strain theory (GST) recognizes that injustice is an aspect of strain that fosters criminal coping in multiple contexts, it does not detail the additive and interactive effects that these types of injustice may have on crime. Nevertheless, GST can provide a useful theoretical lens for understanding how injustice facilitates criminal behavior. This article provides an overview of major findings regarding the relationship between injustice and crime according to a GST framework, concluding with a discussion of new directions for future research.